Interactions between figs (Ficus spp., Moraceae) and fig wasps (Chalcidoidea, Agaonidae) - Ware, Anthony Brian (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1993)
Fig trees (Ficus spp., Moraceae) and fig wasps (Chalcidoidea, Agaonidae) are uniquely associated. In one fig wasp group, the pollinators (Agaoninae), each species is generally host species-specific. The relationship is one of obligate mutualism where the wasps provide pollination services and in return utilises some of the ovules for larval development. Non-pollinating fig wasps (generally belonging to subfamilies other than the Agaoninae) may be gallers or parasitoids, and can also be host species-specific. In the accompanying studies we examined the factors governing the interactions between fig wasps and their host trees. Surveys of fig trees and their associated pollinating fig wasps conducted in southern Africa, Madagascar and The Comores generally confirmed their specific relationships. An examination of F. sycomorlls in Madagascar resulted in the reclassification of F. sakalavarum as a distinct species with its own specific pollinator species. Biological and chemical evidence is presented demonstrating that the pollinators were able to distinguish their hosts through volatiles which emanated from the figs when they were ready to be pollinated. Environmental factors were found to influence wasp behaviour. Ambient temperature governed the timing of wasp emergence from their natal figs. When dispersing from their natal figs, the fig wasps flew upwards and then were blown downwind. Once nearing trees bearing figs ready to be pollinated, the wasps lost height and flew upwind towards the trees. E. baijnathi females apparently avoided figs which already contained a conspecific foundress. Scanning electron microscope studies of pollinating female fig wasp antennae showed that while all the species possessed multiporous plate sensilla, in only a few species were these sensilla elongated. Multiporous plate sensilla elongation is rare or absent among other female chalcids and may have evolved within the Agaoninae in order to facilitate their location on receptive host figs. Pollinator choice specificity appears to break down in a number of cases. In the first case examined, two pollinator species were recorded from the figs of African F. sycomorus. One. C. arabicus, pollinates the figs while the other, C. galili, acts as a 'cuckoo' by utilising some of ovules for oviposition without providing pollen. In the second case three pollinating fig wasp species were recorded from the rigs of F. lutea. Two were found to be incidental visitors and were not specifically attracted to the tree. The hybrid seeds from these crosses were successfully germinated but the seedlings did not grow passed the cotyledon stage of their development. In the concluding study the consequences of Ficus phenology and the structure of the fig's unusual inflorescence on the nonpollinating fig wasp community were examined. Various factors affecting the population levels and species richness were also examined. Future possible research directions were discussed.
Keywords: Fig -- South Africa; Fig wasp -- South Africa; Pollination; Agaonidae; Chalcid wasps